Measurements of antibiotic use in United States dairy systems - Schrag, Nora Francine Ditmars (Kansas State University, 2019)
Methods of measuring antibiotic use were explored using data collected from a convenience sample of 29 US dairy farms for the calendar years of 2016 and 2017. Multiple on-farm data sources included handwritten records and four software systems. Data from each source were standardized to a common format for analysis. Antimicrobial use is reported as regimens per cow year with the regimens defined at the product level by route of administration, number of administrations, time frame between first and last administration, grams per regimen, and grams per administration. The primary goal of this study was to identify which measures might be useful for guiding stewardship at the farm level, and to describe the nuances associated with different methods of measurement. For this reason, care was taken to maintain the association between use and the reason for use (detected disease) for all measures reported. This method of reporting provided enough granularity to compare different methods of antimicrobial use measurement. Measurements of overall use by regimens per cow year indicate that most use occurs as intramammary treatments and cephalosporins are the most commonly used antibiotic class. Use measured by grams per cow year indicates that both Dry Cow therapy and non-intramammary (Other Treatments) contribute significantly to overall use, and use in the penicillin class predominates. Comparisons of measures by regimens, grams, defined daily doses (DDD), defined course doses (DCD) and days of therapy (DOT) are evaluated at the farm level. With the exception of grams, all comparisons of these measures have correlations greater than 0.7 for all categories of use. Potency confounds measures of active substance weight causing use measured as grams of antimicrobial to not correlate as well with other measures (correlations <0.5). This lack of correlation is especially apparent for dry cow therapy where the correlation between grams and other measures is -0.06. These comparisons raise questions about the relationship between use measures and resistance selection pressure. Further study is needed to identify the exact relationship between use measures and resistance selection pressure, as well as to identify treatment outcome parameters that should be assessed to ensure that animal welfare is appropriately monitored as antimicrobial stewardship is advanced.
Keywords: Antibiotic; Antimicrobial; Use; Metrics; Dairy; Cattle